ZAMAN AKHIR ORDE BARU DAN PERUBAHAN SUARA LOKAL DALAM SASTRA INDONESIA - Michael Bodden (HISKI, 2005)
The conscious pattern of most Indonesian literary works presents a portrait of local culture as a conservative